Associations between nutritional status and cognitive impairment in older adults: results from the NHANES 2011–2014 cycles - Xuehe Zhang; Long Yang; Zhong Wang; Hanxiao Wang; Shiyu Nie; Chunxiu Zhao; Shengnan Kang; Chuan Zhang; Chuanliang Pan (Frontiers in Nutrition, 2025)
BackgroundThe Controlling Nutritional Status (CONUT) score is used to assess nutritional status. Given that malnutrition increases the risk of cognitive impairment, this study aimed to clarify the relationship between the CONUT score and cognitive impairment in older adults.MethodsOlder adults aged 60–80 years in the National Health and Nutrition Examination Survey (NHANES) cycles were included in this study. Cognitive impairment was identified according to three different cognitive assessment methods. The degree of malnutrition was assessed by calculating the CONUT score and categorized into normal nutrition (CONUT 0–1) and malnutrition (CONUT 2–12) groups based on the score. Independent associations between the CONUT score and cognitive impairment were examined using logistic regression, while non-linear associations between the CONUT score and cognitive impairment were investigated using restricted cubic splines (RCS).ResultsThe mean participant age was 69.19 years, and approximately 1478 participants (53.6%) had cognitive impairment. According to the CONUT score, the incidence of cognitive impairment was significantly greater in the malnutrition group. According to the adjusted logistic regression analysis, the CONUT score was associated with cognitive impairment (OR: 1.133, 95% CI: 1.052, 1.221; P = 0.002). Cognitive impairment was also associated with the malnutrition group (OR: 1.259, 95% CI: 1.039, 1.524; P = 0.021). RCS analysis revealed L-shaped associations between the CONUT score and cognitive impairment (non-linear p < 0.001).ConclusionElevated CONUT scores are associated with an increased prevalence of cognitive impairment in older adults, potentially aiding in identifying individuals at risk of cognitive decline.